2014
DOI: 10.3928/01913913-20140311-01
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Chloral Hydrate Sedation for Pediatric Ophthalmic Procedures: A Retrospective Review

Abstract: The use of chloral hydrate sedation for ophthalmic evaluation and imaging was safe and effective in this patient population with a high rate of procedure completion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…One was a case report of accidental CH overdose,10 five papers concerned electrodiagnostic testing (EDT),11–15 one paper pertained to IOP measurement,16 and the remaining studies reported on medium to large series of patients being sedated for a variety of ophthalmic examinations (eg, refraction, ocular imaging, contact lens fitting, suture removal, EDTs, etc) 3 4 17–19. One report evaluated the cost-effectiveness of clinic-based CH sedation in comparison to general anaesthesia for paediatric ophthalmic examinations 5…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One was a case report of accidental CH overdose,10 five papers concerned electrodiagnostic testing (EDT),11–15 one paper pertained to IOP measurement,16 and the remaining studies reported on medium to large series of patients being sedated for a variety of ophthalmic examinations (eg, refraction, ocular imaging, contact lens fitting, suture removal, EDTs, etc) 3 4 17–19. One report evaluated the cost-effectiveness of clinic-based CH sedation in comparison to general anaesthesia for paediatric ophthalmic examinations 5…”
Section: Resultsmentioning
confidence: 99%
“…In the recent large series (West et al 3 with 1509 episodes, Wilson et al 4 with 380 procedures, and Burnett et al 5 with 122 cases), more extensive vital sign monitoring is reported, including heart rate, respiratory rate and oxygen saturation, either continuously3 or every 5–10 min 4 5…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations